2020
DOI: 10.1007/s10495-020-01626-0
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid upregulates the expression of the p75NTR/sortilin receptor complex to induce neuronal apoptosis

Abstract: The antiepileptic and mood stabilizer agent valproic acid (VPA) has been shown to exert anti-tumour effects and to cause neuronal damage in the developing brain through mechanisms not completely understood. In the present study we show that prolonged exposure of SH-SY5Y and LAN-1 human neuroblastoma cells to clinically relevant concentrations of VPA caused a marked induction of the protein and transcript levels of the common neurotrophin receptor p75NTR and its co-receptor sortilin, two promoters of apoptotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…One suggested mechanism for the direct activation of apoptosis was the inverse regulation of pro-apoptotic and anti-apoptotic proteins, as combination treatments incorporating HDACi are known to increase the expression of caspases and Bid, and promote the inactivation of the anti-apoptotic proteins XIAP, Bcl-x, RIP, and survivin ( Muhlethaler-Mottet et al, 2006 ). Similarly, the ability of VPA to promote pro-apoptotic neutrophin receptor signaling by upregulating p75NTR and sortilin expression has been identified as an additional mechanism that leads to increased apoptosis of neuroblastoma cells ( Dedoni et al, 2020 ). Pro-nerve growth factor (proNGF) induced activation of p75NTR plays a key role in regulating the survival of neurons and process formation during early development, neuronal death in the developing and aging brain, as well as several neurodegenerative diseases ( Dechant and Barde, 2002 ; Schor, 2005 ).…”
Section: Hdac Inhibitors In Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…One suggested mechanism for the direct activation of apoptosis was the inverse regulation of pro-apoptotic and anti-apoptotic proteins, as combination treatments incorporating HDACi are known to increase the expression of caspases and Bid, and promote the inactivation of the anti-apoptotic proteins XIAP, Bcl-x, RIP, and survivin ( Muhlethaler-Mottet et al, 2006 ). Similarly, the ability of VPA to promote pro-apoptotic neutrophin receptor signaling by upregulating p75NTR and sortilin expression has been identified as an additional mechanism that leads to increased apoptosis of neuroblastoma cells ( Dedoni et al, 2020 ). Pro-nerve growth factor (proNGF) induced activation of p75NTR plays a key role in regulating the survival of neurons and process formation during early development, neuronal death in the developing and aging brain, as well as several neurodegenerative diseases ( Dechant and Barde, 2002 ; Schor, 2005 ).…”
Section: Hdac Inhibitors In Neuroblastomamentioning
confidence: 99%
“…Pro-nerve growth factor (proNGF) induced activation of p75NTR plays a key role in regulating the survival of neurons and process formation during early development, neuronal death in the developing and aging brain, as well as several neurodegenerative diseases ( Dechant and Barde, 2002 ; Schor, 2005 ). Prolonged exposure of SH-SY5Y cells to VPA further predisposed the cells to proNGF-induced cell death, triggering apoptosis through JNK-mediated caspase and PARP cleavage ( Dedoni et al, 2020 ). Additionally, studies evaluating the radiosensitization effect of HDACi also observed impairment of DNA repair mechanisms by downregulation of the DNA repair enzyme Ku-86 upon combination with vorinostat ( Mueller et al, 2011 ).…”
Section: Hdac Inhibitors In Neuroblastomamentioning
confidence: 99%
“…Entinostat was also found to induce a greater enhancement of CASZ1 levels in SH-SY5Y, and LAN-1 cells. These findings suggest that the superior efficacy of entinostat in inducing p75NTR was the result of a greater action on the epigenetic machinery that controls the expression of the neurotrophin receptor in neuroblastoma cells [ 17 , 18 , 19 ]. The induction of p75NTR by entinostat occurred within a concentration range (0.1–1.0 µM) which correlated with the reported micromolar potency of the drug in inhibiting HDAC activity [ 31 ] and with the plasma concentrations that were required to produce anti-cancer effects in clinical trials [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the exposure to HDAC inhibitors caused the downregulation of TrkB expression and signaling [ 15 ], which promote neuroblastoma cell survival and aggressiveness [ 9 , 10 ], and the upregulation of the truncated isoform of TrkC that is associated with neurotrophin 3-induced apoptosis [ 16 ]. Moreover, the treatment of neuroblastoma cells with HDAC inhibitors upregulated the expression of the common neurotrophin receptor p75NTR and the co-receptor sortilin, thus allowing the execution of proNGF-induced cell death [ 17 ]. The induction of p75NTR expression by HDAC inhibitors has been shown to occur through an epigenetic mechanism involving depletion of the methyltransferase EZH2, a core component of the polycomb repressor complex 2, and the consequent derepression of the transcription factor CASZ1, a positive regulator of the NGFR gene, encoding for p75NTR [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation